A construção do conhecimento agroecológico através da utilização de ferramentas participativas no Projeto "Assentamentos Sustentáveis" nas regiões de Ribeirão Preto e Itapeva, São Paulo - Souza, Tatiane de Jesus Marques (Universidade Federal de São Carlos, 2012)
This study aims discusses the use of participatory methods in agroecological practices developed by the project "Social and environmental capacitation for the building of sustainable development projects in rural settlements in the state of São Paulo" that used as methodology the Participatory Rural Appraisal, the Participatory Action Research and the Participatory Observation. The localities chosen for the discussion, because of the similarity of thematic worked, were two settlements of agrarian reform; the Sepé Tiaraju, that has a sustainable development propose since its formation; and the Pirituba, one of the first settlements in the state, structured in the conventional production system. This paper discussed progresses and challenges related with methodological strategies used in this settlements for the building of agroecological knowledge. Progresses are primarily related to the strategic participation of the project construction, of the process of farmers experimentation and the knowledge exchange executed. The challenges are related to the autonomy of the farmers groups, who were part of the project and to the extension of the type of the public, mainly related to the gender issue of those who were part of the activities.
A discussion about the construction of the agroecologial knowledge through the uitilization of participatory methods in the "sustainable settlements" project
Keywords: Agroecologia; Sistemas Agroflorestais; Metodologias Participativas; Agroecology; Agroforestry Systems; Participative Methodologies; Family Agriculture; Sustainability; CIENCIAS AGRARIAS